Authentic Assessment of Fungi for Vocational School Student: Concept Map, Self Assessment and Performance Test - Nugrahani, Ristiana; Budi Prasetyo, Andreas Priyono; Iswari, Retno Sri (Journal of Innovative Science Education, 2018)
The authentic assessment in biology teaching learning at vocational school of Bawen, SMK Negeri 1 Bawern, especially at the department of  post harvest technology, has not been fully implemented yet. This study was aimed at developing and analyzing the validity, reliability, effectiveness, and practicality of authentic assessment tools such as concept map assessment (CMA), self assessment (SA), and performance assessment (PA) for vocational students. This research used Research and Development (R & D) approaches. Content and construction validities were verified by experts. Concruent and predictive validity  of CMA was  verified by score of correlation between CMA score and master map as well as final semester score. Concruent validity of SA was  calculated from corelation scores of PA and  basic competency 3.5. Concruent and predictive validations were calculated by pearson corelation product moment. Reliability of CMA and PA was analysed by  reliability inter-rater reliability techniques. Reliability of SA was calculated by alpha cronbach’s methods. Effectiveness and praticability of  instruments were calculated from  teachers’s and students’ responses analysed with percentage description techniques. The results showed that the concept map has excellent content and construction validity, excellent concurrency validity, and good predictive validity. Self assessment had excellent content and construction validity and good concurrency validity. PA had excellent content and construction validity and good concurrency validity. CMA is very effective for measuring cognitive aspects, SA is very effective to measure scientific attitudes, and PA of biological process skills. The three types of assessment were  claimed to have practicality in terms of time, ease of use, ease of correction, facility supports, and cost required